Transcatheter arterial embolization for gastrointestinal bleeding related to pancreatic adenocarcinoma: clinical efficacy and predictors of clinical outcome. Issue 123 (February 2020) - Lee, Sang Min; Jeong, So Yeong; Shin, Ji Hoon; Choi, Ho Cheol; Na, Jae Boem; Won, Jung Ho; Park, Sung Eun; Chen, Cheng Shi
Highlights: A highly detected bleeding foci was effectively treated with TAE. Stent-related bleeding was frequent and characteristic angiogram was arterial cut-off. Massive transfusion and TNM stage 4 were related to clinical failure. Abstract: Purpose: To evaluate the clinical efficacy of transcatheter arterial embolization (TAE) for managing pancreatic adenocarcinoma-related gastrointestinal (GI) bleeding, and to determine the factors associated with clinical outcomes. Method: From 2001–2017, this retrospective study included 58 patients who underwent TAE for pancreatic adenocarcinoma-related GI bleeding. The technical and clinical success of TAE, clinical factors including patient characteristics and embolization details, complications, and the 30-day mortality were evaluated. Univariate analyses were performed to determine the factors related to the clinical outcomes. Results: On angiography, bleeding foci were detected in 47 patients (81%), while the other 11 patients showed tumor staining. Technical success rate was 98%, and first session and overall clinical success rates were 79% and 88%, respectively. N-butyl cyanoacrylate (NBCA) was the most commonly used embolic agent (53%). Stent-related bleeding was shown in 22 patients with characteristic angiogram such as arterial cut-off (13/22) and arteriobiliary fistula (5/22), with comparable clinical success rate (82%). Bleeding from the superior mesenteric artery (n = 3) at the first session of angiography and complications (n = 2), such as ischemic hepatitis and small bowel infarction, were all associated with a 30-day mortality. The overall 30-day mortality rate was 22%. Univariate analysis showed that massive transfusion and TNM stage 4 were related to clinical failure (P = 0.035 and 0.038, respectively). Conclusions: TAE was effective and safe for pancreatic adenocarcinoma-related GI bleeding. Stent-related bleeding was not uncommon, and associated with vascular abnormality amenable to TAE. Massive transfusion and TNM stage 4 were related to clinical failure.